Psychological health of the future teacher in the process of professional development within the framework of the ecopsychological approach - Irina S. Filonenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The development of a high level of psychological health among university students is closely connected with an active life and professional position, or in other words, with their subjectivity. In conditions of the ecopsychological approach to the development of the psyche, the subjective qualities of the student must go through seven stages. According to the principle of fractality, the effectiveness of the development of each stage is determined by the development of seven cognitive-regulatory abilities in their subject. The importance of strengthening the psychological health of students is especially relevant today, when the main indicator of personality-oriented education is the interaction and mutual development of the personalities of the teacher and student, and the development of a system of professional values and goals of future teachers begins during university training. The research is aimed at identifying priority vectors of psychological health among university students at various stages of subjectivity formation, and their relationship with cognitive-regulatory abilities that ensure the formation of each of the stages, as well as to determine the development of the structure of psychological health. The study was conducted by methods of diagnostics of the stages of subjectivity development, the ability to perform educational actions and "Individual model of psychological health". This pilot study shows the relationship between the components of the model of psychological health of future teachers, the process of subjectivity development and fostering the ability to perform educational actions during their studies at the university. If at the beginning of the training, the interaction of students in a group was at the initial stage, students were just beginning to show their individuality, reveal their creative abilities, then by the end of the training, communication in a group, joint activity, creative expression and self-expression became more significant.